Characterization of an acoustically coupled multilayered microfluidic platform on SAW substrate using mixing phenomena - Kishor, Rahul (2016)
Optimization of the reusable microfluidic platform on surface acoustic wave (SAW) requires a clear understanding of the various factors that affects the acoustic energy transmission to the fluid in the microchannel. This article reports the characterization and analysis of the reusable SAW microfluidic platform. The acoustic energy transfer through various layers was characterized by the microfluidic mixing phenomenon. During this work, mixing efficiency was considered to evaluate the acoustic energy transmission. The three different parameters taken into consideration are the input voltage, SAW frequency and the coupling layer thickness. The effect of the factors on the output response is examined by conducting experimental studies and developing new analytical models. The acoustic wave was coupled through a liquid layer to a disposable superstrate. The anti-symmetric higher order lamb waves generated on thin glass plate generates compressional waves in the liquid to induce fluid motion. The acoustic energy delivered to the fluid increased as the square of the applied voltage and saturated at 50 V. The frequency response demonstrated a higher acoustic energy transmission for the 100MHz compared to the 50MHz, which was validated by numerical studies. Power transmitted through the coupling layer displayed a sinusoidal dependence on the normalized thickness of the layer. Finally, the effect of temperature is also considered to confirm the validity of the developed models